Problematic mobile phone use among adolescents with mild intellectual disability - Glumbić Nenad; Brojčin Branislav; Žunić-Pavlović Vesna; Đorđević Mirjana (Psihologija, 2020)
This study was conducted with the aim to determine the frequency and predictors of problematic mobile phone use in adolescents with mild intellectual disability (MID) and typically developing adolescents (TDA). The sample included 623 TDA and 67 adolescents with MID. The Mobile Phone Problem Use Scale, Loneliness and Social Dissatisfaction Scale, and Rosenberg Self-Esteem Scale were used as primary outcome measures. The percentage of MID and TDA participants with problematic mobile phone use was 11.9% and 9.8% respectively, but there were twice as many participants who belong to the risk group among the participants with MID (20.9%) than among TDA ones (10.2%). Problematic use of mobile phones was related to the number of years of mobile phone usage, more frequent use, female gender, younger age, as well as with a lower level of self-esteem, and a higher level of loneliness. This study showed that almost every third adolescent with MID is having problematic or risky mobile phone use.